Clinical Characteristics and Mortality of Non-tuberculous Mycobacterial Infection in Immunocompromised vs. Immunocompetent Hosts - Chai, Jingjing; Han, Xu; Mei, Qimin; Liu, Tao; Walline, Joseph Harold; Xu, Jia; Liu, Yecheng; Zhu, Huadong (Frontiers in Medicine, 2022)
Immunosuppression and host vulnerability play a key role in nontuberculous mycobacteria (NTM) pathogenesis. The objective of this study was to compare the clinical characteristics and mortality of NTM infections in immunocompromised and immunocompetent patients. We used a retrospective dataset obtained from our large, tertiary, urban, teaching hospital which is the medical records of hospitalized patients with NTM infections between January 1, 2013 to December 31, 2020. The information including clinical manifestations, imaging, and NTM etiological data were obtained from the hospital’s clinical data system. A total of 480 patients with NTM infections completed species identification. 118 hospitalized NTM patients who met ATS/IDSA NTM diagnostic criteria and had complete medical records were included in the study. The average age was 49.4 years, 57 (48.3%) were female, and 64 (54.2%) were immunosuppressed host. In our study, the most common species in order of frequency were: M. intracellulare, M. abscessus, M. avium, and M. kansasii among NTM patients. The most common comorbidity was history of previous tuberculosis (30.5%). Besides malignancy, the most common immunodeficiencies were adult-onset immunodeficiency induced by anti-interferon-gamma autoantibody, SLE, and vasculitis. The immunocompromised patients with NTM had more clinical symptoms, comorbidities and lower lymphocyte counts compared to immunocompetent patients. The mortality we observed in immunocompromised patients of NTM disease was significantly higher than that of immunocompetent patients (HR 3.537, 95% CI 1.526-8.362). Immunosuppressed NTM patients with lower B and CD4+ T lymphocyte counts may more frequently present with disseminated NTM infections, clinical exacerbations, and higher mortality than immunocompetent patients.